Microsoft Word 2007: A Professional Approach - Hinkle Deborah (Mc Graw Hill Irwin, 2007)
The Professional Approach Series is designed for students unfamiliar with the Microsoft Office Suite, or even students who are nervous about trying to learn computer skills. It is ideal for students who are new to the world of computers, yet in-depth enough to teach and challenge more savvy users. Each lesson contains up to 25 skill-applications and 5 end-of-unit skill-applications that take students from simple to complex situations. The Office 2007 texts complete instruction in all skill sets and activities for the appropriate MCAS Exams.